Design thinking : process and methods manual - Curedale, Robert, ....- (Topanga : Design Community College, 2013)
This book is the most extensive reference available to Design Thinking. Design Thinking is an approach to designing products, services, architecture, spaces and experiences that is being quickly adopted by designers, architects and some of the world's leading brands such as GE, Target, SAP, Procter and Gamble, IDEO and Intuit. It is being taught at leading universities including Stanford and Harvard. Design Thinking creates practical and innovative solutions to problems. It drives repeatable innovation and business value. Design Thinking can be used to develop a wide range of products, services, experiences and strategy. It is an approach that can be applied by anyone. This book is an indispensable Design Thinking reference guide for: -Architects, industrial designers, interior designers, UX and web designers, service designers, exhibit designers, design educators and students, visual communication designers, packaging and fashion designers, all types of designers -Engineers and Marketing professionals -Executives and senior business leaders -Decision makers in R&D of products, services, systems and experiences -School teachers and school students